2012
DOI: 10.1007/978-3-642-32147-4_32
|View full text |Cite
|
Sign up to set email alerts
|

The Gram Dimension of a Graph

Abstract: The Gram dimension gd(G) of a graph is the smallest integer k ≥ 1 such that, for every assignment of unit vectors to the nodes of the graph, there exists another assignment of unit vectors lying in R k , having the same inner products on the edges of the graph. The class of graphs satisfying gd(G) ≤ k is minor closed for fixed k, so it can characterized by a finite list of forbidden minors. For k ≤ 3, the only forbidden minor is K k+1 . We show that a graph has Gram dimension at most 4 if and only if it does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…It is straightforward to see that both invariants are non-increasing with respect to edge and vertex deletion. However, unlike a related parameter of Gram dimension introduced in [22], the properties mlt(G) ≤ k and gcr(G) ≤ k are not minorclosed as the following example shows. Example 1.7.…”
Section: Generic Completion Rank and Maximum Likelihood Thresholdmentioning
confidence: 96%
“…It is straightforward to see that both invariants are non-increasing with respect to edge and vertex deletion. However, unlike a related parameter of Gram dimension introduced in [22], the properties mlt(G) ≤ k and gcr(G) ≤ k are not minorclosed as the following example shows. Example 1.7.…”
Section: Generic Completion Rank and Maximum Likelihood Thresholdmentioning
confidence: 96%
“…This parameter was introduced in [53,54] and its study is motivated by its connection with the low rank positive semidefinite matrix completion problem. In [53,54] it is shown that, for any fixed k 1, the class of graphs satisfying gd.G/ Ä k is closed under taking minors.…”
Section: Problemmentioning
confidence: 99%
“…In [53,54] it is shown that, for any fixed k 1, the class of graphs satisfying gd.G/ Ä k is closed under taking minors. Moreover, it is shown that K kC1 is the only minimal forbidden minor for k 2 f1; 2; 3g and that K 5 and K 2;2;2 are the only minimal forbidden minors for the graph property gd.G/ Ä 4.…”
Section: Problemmentioning
confidence: 99%
See 2 more Smart Citations